Host miRNAs are involved in hormonal regulation of HaSNPV‐triggered climbing behaviour in Helicoverpa armigera. Issue 2 (9th January 2018) - Zhang, Songdou; An, Shiheng; Hoover, Kelli; Li, Zhen; Li, Xiangrui; Liu, Xiaoming; Shen, Zhongjian; Fang, Haibo; Ros, Vera I. D.; Zhang, Qingwen; Liu, Xiaoxia
Abstract: Baculoviruses manipulate host climbing behaviour to ensure that the hosts die at elevated positions on host plants to facilitate virus proliferation and transmission, which is a process referred to as tree‐top disease. However, the detailed molecular mechanism underlying tree‐top disease has not been elucidated. Using transcriptome analysis, we showed that two hormone signals, juvenile hormone (JH) and 20‐hydroxyecdysone (20E), are key components involved in HaSNPV‐induced tree‐top disease in Helicoverpa armigera larvae. RNAi‐mediated knockdown and exogenous hormone treatment assays demonstrated that 20E inhibits virus‐induced tree‐top disease, while JH mediates tree‐top disease behaviour. Knockdown of BrZ2, a downstream signal of JH and 20E, promoted HaSNPV‐induced tree‐top disease. We also found that two miRNAs target BrZ2 and are involved in the cross‐talk regulation between 20E and JH manipulating HaSNPV replication, time to death and HaSNPV‐induced tree‐top disease.